2021
DOI: 10.1101/2021.10.01.462786
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Chi3l1 is a modulator of glioma stem cell states and a therapeutic vulnerability for glioblastoma

Abstract: Chi3l1 (Chitinase 3-like 1) is a secreted protein highly expressed in glioblastoma. Here, we show that exposure of glioma stem cells (GSCs) to Chi3l1 reduces the CD133+/SOX2+ cells and increases the CD44+/Chi3l1+ cells. Chi3l1 binds to CD44 and induces phosphorylation and nuclear translocation of beta-catenin, Akt and STAT3. Single cell RNA-seq and RNA velocity following incubation of GSCs with Chi3l1 show significant changes in GSC state dynamics driving GSCs towards a mesenchymal expression profile and reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…CHI3L1 is prominently expressed in these tumors where it predicts radiation resistance and a poor prognosis (57). More recent investigations from our laboratory and others, also demonstrated that CHI3L1 drives mesenchymal differentiation of GBM stem cells (58) and that EGFR amplification is also a prominent feature of GBM. Based on these findings it is tempting to speculate that interactions such as the ones described above in NSCLC are operative in these other disorders.…”
Section: Discussionmentioning
confidence: 64%
“…CHI3L1 is prominently expressed in these tumors where it predicts radiation resistance and a poor prognosis (57). More recent investigations from our laboratory and others, also demonstrated that CHI3L1 drives mesenchymal differentiation of GBM stem cells (58) and that EGFR amplification is also a prominent feature of GBM. Based on these findings it is tempting to speculate that interactions such as the ones described above in NSCLC are operative in these other disorders.…”
Section: Discussionmentioning
confidence: 64%
“…Remarkably, neutralization of CHI3L1 is sufficient to restore iNKT cell activity, even in the presence of exogenous CHI3L1 supplementation. CHI3L1 can signal through CD44, one of its physiological receptors (34)(35)(36), which is upregulated in Pg-primed iNKT cells (Figure 3B). This signalling may act as an immune checkpoint to suppress iNKT cell activation via the PI3K/AKT pathway, a known repressor of STAT3 transcription (Figure 5F) (22,(37)(38)(39), but warrants further investigations.…”
Section: Discussionmentioning
confidence: 99%
“…4h, Supplementary Fig. 4d), expressing CHI3L1, HGD and SLC4A10, which are linked to stemness and neuronal excitability [42][43][44]. Moreover, analysis of gene signatures linked to singlecell transcriptional states in GBM revealed that both OS21-8 and OS21-3 derived fractions share levels of the astrocytic-like program (Fig.…”
Section: Tertp Mutation and Single-cell Transcriptomic Heterogeneitymentioning
confidence: 95%